Ragam Makna Pada Slogan Iklan Produk Minuman Berbahasa Indonesia - Gaudiswari, Ramadhaniar Rizky; Iriyansah, Muhamad Rinzat; Firmansyah, Dodi (Peneliti.net, 2024)
This study aims to analyze the variety of meanings using semantic studies by focusing the study on advertising slogans for beverage products in Indonesian because there are many advertising slogans and are easy to remember by the public. This study describes the lexical, grammatical, referential, and non-referential meanings of Indonesian beverage product advertising slogans. This study uses a qualitative descriptive method, the data collection technique used is the listening and note-taking technique. The results of the analysis obtained on 10 advertising slogans for beverage products in Indonesian language are that there are four meanings in the slogansincluding lexical meaning as many as 24 words, grammatical meaning as many as 12 words, referential as many as 7 words, and non-referential as many as 2 words.